Treatment of Zenker's Diverticulum With Endoscopic Stapled Esophago-divertisculostomy (ESD): Analysis of Long-term Outcome. Issue 6 (December 2017) - Mazza, Michele; Bergamini, Alberto N.; Parise, Paolo; Cossu, Andrea; Adamenko, Olga; Elmore, Ugo; Rosati, Riccardo
Abstract : Background: Endoscopic Zenker diverticulum (ZD) treatment has become quite common because of the low complication rates, reduced procedure time, and shorter hospital stay. Many endoscopic treatments are available including the endoscopic stapled esophago-diverticulostomy (ESD). Many data regarding ESD are available on the short-term outcomes, but few on the long-term ones. Materials and Methods: From March 1998 to July 2016, 126 patients with ZD were candidate for ESD. Since 2009, 2 stay sutures were routinely positioned at the lateral edges of the septum using Medtronic Endostitch 10 mm suturing device. Demographic and perioperative data, symptoms, and surgical outcomes were recorded. Long-term ESD results were analyzed. An extra-analysis on the surgical outcome was performed comparing patients treated with or without stay sutures. Results: In total, 117 patients successfully underwent ESD. The mean age was 69.9 years with a male predominance. Intraoperative complications occurred in 6.8% of cases. Only 2.6% of the patients reported postoperative complications. For the long-term analysis, we were able to contact 92 patients for a mean period follow-up of 65.3 months. At 6-month outpatient visit 77.68% of patients were completely asymptomatic. In total, 22.3% of the patients needed an extratreatment due to incomplete section of the septum, reaching a success rate of 95.5%. The long-term resolution rate remained high (91.3%). The use of stay sutures did not statistically influence the operative time (22.8 vs. 26.7 min, P =0.070), nor intraoperative and postoperative complication rate, but a statistically significant higher complete resolution rate of symptoms with a single session of ESD was observed respect those treated without (87.3% vs. 65.3%, respectively). Conclusions: ESD is a safe and effective treatment of ZD and it can control symptoms even in a long-term follow-up. In our experience, the use of stay sutures placed with Endostitch increases short and long-term results reducing the need for further treatments.